Defective Structures in Metal Compounds for Energy‐Related Electrocatalysis. Issue 2 (16th November 2020) - Yan, Xuecheng; Jia, Yi; Yao, Xiangdong
Abstract : Catalysts play a critical role in accelerating the electrochemical reactions. Engineering the electronic structures and surface properties of electrocatalysts is a feasible approach to improve their catalytic performance. Introducing defects such as anion and cation vacancies into transition metal‐based materials to enhance their activity for various energy‐related electrocatalytic reactions has been receiving increasingly attention in recent years. In this review, a systematic summary of the anion and cation defects on different electrochemical reactions will be presented. In particular, the commonly used methods to produce anion vacancies (such as oxygen, sulfur, and phosphorus defects) and cation vacancies (such as Fe, Co, and Ni defects) will be discussed. The control of the defect density and refilling heteroatoms to stabilize the anion defects and simultaneously to further enhance their catalytic performance are also summarized. In addition, recent work on creating multivacancies in transition metal‐based electrocatalysts for maximizing their catalytic activities is reviewed as well. Finally, future research on defect engineering in metal compounds for electrocatalysis is proposed. This review will guide the further development of various energy‐related electrocatalytic reactions promoted by defective structures in metal composites. Abstract : Defect engineering such as introduction of anion and cation vacancies into transition metal‐based materials is a feasible and effective strategy to regulate their electronic structures and surface properties. This review summarizes recent studies on controllably creating the anion (such as oxygen, sulfur, and phosphorus) and cation (such as iron, cobalt, and nickel) vacancies for optimizing the electrocatalytic performance of metal‐based compounds.